Additive effects of Trichoderma isolates for enhancing growth, suppressing southern blight and modulating plant defense enzymes in tomato - Nusrat Jahan Mishu; Md. Robiul Hasan; Shah Mohammad Naimul Islam; Jannatun Nayeema; Md. Motaher Hossain (PLoS ONE, 2025)
Southern blight, caused by Sclerotium rolfsii, poses a significant economic threat to tomato cultivation. This study involved the isolation, characterization, and evaluation of three selected Trichoderma isolates (Tri2, Tri3, and Tri6), applied individually and in combination, for their potential to promote plant growth and suppress southern blight under both in vitro and in vivo conditions. These isolates exhibited multiple plant growth-promoting traits, including cellulase, protease, amylase, lipase, catalase, and phosphate-solubilizing activities. Furthermore, they performed as efficient antagonists, inhibiting the mycelial growth by up to 88.8% and the oxalic acid production of S. rolfsii by up to 81.9%. The Trichoderma isolates significantly enhanced tomato seed germination and seedling vigor (p < 0.05). In seed tray and pot, experiments, consortium treatments (dual and triple application) demonstrated significantly greater plant height (≤168.8%), biomass (≤507.3%), leaf number (≤150%), leaf diameter (≤86.2%), chlorophyll content (≤322%), stem diameter (≤129.1%), gas exchange parameters, and root colonization than control and single treatments (p < 0.05). Additionally, these consortium treatments exhibited significantly higher efficacy in reducing damping-off (≤92%) and southern blight severity (≤80%) caused by S. rolfsii, compared to untreated plants (p < 0.05). Biochemical analyses revealed that Trichoderma-treated plants challenged with S. rolfsii showed reduced oxidative stress, evidenced by lower hydrogen peroxide (H₂O₂) and malondialdehyde (MDA) levels. The treatments also increased osmoprotectant levels such as soluble sugars, proline, phenolics, and flavonoids, along with the activities of defense-related enzymes, including peroxidase (PO), polyphenol oxidase (PPO), and phenylalanine ammonia-lyase (PAL), compared to S. rolfsii-infected controls (p < 0.05). Under field conditions, treating S. rolfsii-inoculated plants with Trichoderma isolates, whether singly, in pairs, or as a trio, significantly increased plant height, yield, and fruit Brix content (p < 0.05). The consortium application (Tri2 + Tri3 and Tri2 + Tri3 + Tri6) led to the highest increases in plant height (≤94%), fruit number (≤114%), yield (≤19.59 t/ha), and Brix (≤4.88). These findings suggest that the additive interactions among Trichoderma isolates enhance tomato growth and suppress S. rolfsii, offering an eco-friendly and effective strategy for managing southern blight.